Fast inactivation of Shal (K(v)4) K+ channels is regulated by the novel interactor SKIP3 in Drosophila neurons. - Diao, F.; Waro, G.; Tsunoda, S. (Molecular and Cellular Neurosciences, 2009)
Shal K+ (K(v)4) channels across species carry the major A-type K+ current present in neurons. Shal currents are activated by small EPSPs and modulate post-synaptic potentials, backpropagation of action potentials, and induction of LTP. Fast inactivation of Shal channels regulates the impact of this post-synaptic modulation. Here, we introduce SKIP3, as the first protein interactor of Drosophila Shal K+ channels. The SKIP gene encodes three isoforms with multiple protein-protein interaction domains. SKIP3 is nervous system specific and co-localizes with Shal channels in neuronal cell bodies, and in puncta along processes. Using a genetic deficiency of SKIP, we show that the proportion of neurons displaying a very fast inactivation, consistent with Shal channels exclusively in a "fast" gating mode, is increased in the absence of SKIP3. As a scaffold-like protein, SKIP3 is likely to lead to the identification of a novel regulatory complex that modulates Shal channel inactivation.